Security on peer to peer networking in energy internet - Jianwei REN; Chunyan AN; Yun LIU; Jian LI (Dianxin kexue)
Peer to peer systems are widely deployed in the internet.Its self-healing and self-organizing framework will facilitate plug and play,high reliability and other features of the energy internet.But it brings new threat.The abstract features were researched.The threats introduced by peer to peer networking in the energy internet scenario were analyzed,and accordingly countermeasures were given.